An economic evaluation of tofacitinib for the treatment of moderately-to-severely active ulcerative colitis: modeling the cost of treatment strategies in the United States. (2nd September 2019) - Milev, Sandra; DiBonaventura, Marco daCosta; Quon, Peter; Wern Goh, Jo; Bourret, Jeffrey; Peeples-Lamirande, Kathleen; Soonasra, Arif; Cappelleri, Joseph C.; Quirk, Daniel
Abstract: Aims: To evaluate the cost differences between a treatment strategy including tofacitinib (TOFA) vs treatment strategies including adalimumab (ADA), golimumab (GOL), infliximab (IFX), and vedolizumab (VEDO) among all patients with moderate-to-severe ulcerative colitis (UC) (further stratified by patients naïve/exposed to tumor necrosis factor inhibitors [TNFis]). Materials and methods: An Excel-based decision-analytic model was developed to evaluate costs from the perspective of a third-party US payer over 2 years. Efficacy and safety parameters were taken from prescribing information and published trials. All patients started induction therapy on the first treatment in the strategy and continued if efficacy criteria were met and no major adverse event occurred (in which cases they proceeded to the next treatment in the strategy). Results: The cost per member per month (PMPM) of the TOFA–>IFX–>VEDO–>GOL strategy (1.11) was lower than that of the ADA–>IFX–>VEDO–>GOL strategy (1.34; Δ = −0.23) among the TNFi-naïve population ( n = 204 patients out of a plan of one million members). Similarly, the use of TOFA before ADA (i.e. TOFA–>ADA–>IFX–> VEDO) was also associated with lower PMPM costs than the use of ADA before TOFA (i.e. ADA–>TOFA–>IFX–>VEDO): 1.15 vs 1.25 (Δ = −0.10). Similar, and often larger, differences were observed in both the overall moderate-to-severe population and the TNFi-exposed population. Sensitivity analyses resulted in the same conclusions. Limitations: Our model relied on efficacy data from prescribing information and published trials, which were not head-to-head and slightly differed with respect to methods. Additionally, our model used representative minor and major ADRs (and the associated costs) to represent toxicity management, which was a simplifying assumption. Conclusions: This analysis, the first of its kind to evaluate TOFA vis-à-vis other advanced therapies in the US, suggests the early use of TOFA among both TNFi-naïve and TNFi-failure patients results in lower PMPM costs compared with other treatment alternatives.